THE CHALLENGE AND THREAT OF OCCUPATIONAL STRESS IN THE 21st CENTURY - ERNEST I. ACHALU, ERNEST ACHALU (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
Work can have both positive and negative effects on workers health. Work can serve as means of economic survival ant! happiness but it can also expose workers to occupational hazards that pose seRous threat to health and well being of the worker and their organization. These hazards can lead to occupational stress, diseases, accidents and injury induding death. The promotion of health, safety and welfare of workers in the face of rapid industrialization and high level of occupational stress in developing countries without the basic occupational health service and hazard control measures are a mjor problem facng health educators and other health professionals in the 21st century. This paper examines the nature of occupational stress, causes or sources of occupational stress, consequences of occupational stress on the worker and organization as well ass strategies to cope with occupational stress at individual and organization levels.